Proyecto de factibilidad para la implementación de una empresa procesadora y comercializadora de pulpa de kumpia (renealmia alpina) en el cantón Gualaquiza de la provincia de Morona Santiago, para el año 2015 - Unkuch Nantipia, Glenda Georgina (2016)
This research was conducted in the canton Gualaquiza, Sucumbios Province, with the main objective of the feasibility study for the implementation of a producer and marketer of pulpa de Kumpia paste in the aforementioned canton company. For this purpose based on methods such as inductive, deductive, statistical and synthetic, besides the application of research techniques such as direct observation and the application of surveys to a sample of 377 consumer families pulpa de Kumpia paste analysis was performed in Gualaquiza Canton. Using the methodology described market research where it was known that there is an unmet demand for 82 065 units pulpa de Kumpia paste 100 grams for the first year of life of the project took place. On the technical study it determined that the installed capacity of the plant is 71,000 units pulpa de Kumpia paste 100g. Like any production process can not be started with 100% of its capacity due to several factors including market opening, selection of intermediaries engaging in the production process, personnel training, etc. Therefore it is planned to start with the 85% of the installed capacity of the plant, that is, in the first year of operation of the company 60,350 units will be produced pulpa de Kumpia paste. For the second year, it increased by 5% of production, ie 63,900 units and from the third year onwards, will be increased to 95%, ie 67,450 units pulpa de Kumpia paste to be marketed in Gualaquiza by of the new company. The plant will be located in the city of Gualaquiza, at Eloy Alfaro y Gonzalo Pezantez of that canton, which according to the application microlocalization matrix was found to have the highest rating compared to two other options presented, front critics weighting factors as proximity to customers, access roads and communications, transport, infrastructure and basic services. As for project engineering the production process occurs with all stages regarding the development of the units in pulpa de Kumpia container of 500 grams. In the administrative organization and then the corresponding analysis has determined the implementation of a limited liability company, company name the company used is Pulpa de Kumpia La Amazónica S.A. By the favorable conditions that allow us to offer high quality products, obtain profitability and above all implement jobs.